(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
Blended learning has become increasingly important in Taiwanese higher education, particularly in creative disciplines such as fashion design. With the rapid advancement of digital tools and the growing emphasis on technology in education, blended learning provides fashion design students with greater flexibility to engage with both theory and practice. Despite its growing adoption, research into its impact on fashion design education remains limited. This study seeks to address this gap by examining how blended learning influences academic achievement, self-directed learning (SDL), and critical thinking within Taiwanese fashion design education. Specifically, it investigates how blended learning enhances creative studio practice and fashion-specific learning outcomes. The findings demonstrate significant improvements in SDL and critical thinking, which are key to developing creativity and problem-solving skills in fashion design students. The study underscores the potential of blended learning to bridge the gap between theory and practice in fashion education, offering valuable insights for its optimisation in similar contexts.